2018
DOI: 10.1155/2018/2568235
|View full text |Cite
|
Sign up to set email alerts
|

3D Comparison of Mandibular Response to Functional Appliances: Balters Bionator versus Sander Bite Jumping

Abstract: Aim To assess the three-dimensional (3D) maxillomandibular and dental response to Balters Bionator (BB) and the Sander Bite Jumping Appliance (SBJA) in growing patients. Materials and Methods Twenty-seven Class II division 1 patients (13 males, 14 females), consecutively treated with either the BB (9 females, 7 males; 10.1 ± 1.6 years) or SBJA (5 females, 6 males; 11 ± 1.9 years), were collected from a single orthodontic practice. All patients presented overjet ≥5 mm, full Class II or end-to-end molar relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Studies using CT scans found an increase in airflow in the oropharynx of patients with skeletal Class II malocclusion treated with functional appliances 21,23 . These appliances seem to keep the tongue in a more advanced position, which indirectly increases posterior airflow space 21 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies using CT scans found an increase in airflow in the oropharynx of patients with skeletal Class II malocclusion treated with functional appliances 21,23 . These appliances seem to keep the tongue in a more advanced position, which indirectly increases posterior airflow space 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The objective of the treatment was to correct the skeletal Class II and Angle Class II division 1 malocclusion. In the first stage, a removable protraction appliance, the Balters Bionator 22,23 , was indicated to stimulate mandibular growth. It should be used all the time, except in the first month, when it should be removed for school activities, for speech adaptation.…”
Section: Treatment Plan and Mechanicsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were in agreement with those reported in the CBCT study by Gazzani et al and others. [31][32][33] The current retrospective study provides a 3D analysis method for the clinical evaluation of TMJ changes. This method has good clinical application prospects for yielding higher accuracy.…”
Section: Discussionmentioning
confidence: 99%